2018
DOI: 10.1155/2018/1657237
|View full text |Cite
|
Sign up to set email alerts
|

A New Surgical Method of U-Shaped Myometrial Excavation and Modified Suture Approach with Uterus Preservation for Diffuse Adenomyosis

Abstract: Objective To evaluate the feasibility, safety, and efficacy of a new surgical method of U-shaped myometrial excavation and modified suture approach with uterus preservation for diffuse adenomyosis. Methods From January 2012 to December 2014, 198 patients with diffuse adenomyosis were surgically treated using this novel procedure in Zhengzhou Hua-Shan Hospital. Degree of dysmenorrhea, menstrual blood volume, serum CA 125, and uterine size before and at 1 month, 3 months, 6 months, 12 months, and 24 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Recently, one study by Kwack et al showed that dysmenorrhea was improved in 100% of the patients with diffuse uterine adenomyosis at the 7-month follow-up after adenomyomectomy using the muscle fold method 23. Another study by Jun-Min et al found that the effective rate was 94.9% in patients with diffuse uterine adenomyosis within 2 years after the U-shaped adenomyomectomy 24. Osada et al reported that the VAS score of dysmenorrhea was decreased from 10.00±0.00 pre-surgically to 1.67±1.79 at 2-year follow-up after the triple-flap method adenomyomectomy in patients with diffuse adenomyosis 22.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study by Kwack et al showed that dysmenorrhea was improved in 100% of the patients with diffuse uterine adenomyosis at the 7-month follow-up after adenomyomectomy using the muscle fold method 23. Another study by Jun-Min et al found that the effective rate was 94.9% in patients with diffuse uterine adenomyosis within 2 years after the U-shaped adenomyomectomy 24. Osada et al reported that the VAS score of dysmenorrhea was decreased from 10.00±0.00 pre-surgically to 1.67±1.79 at 2-year follow-up after the triple-flap method adenomyomectomy in patients with diffuse adenomyosis 22.…”
Section: Discussionmentioning
confidence: 99%
“…We included 38 trials, reporting on data from 5175 women ( Table I ) ( Fedele et al , 1997 ; Maia et al , 2003 ; Hadisaputra and Anggraeni, 2006 ; Bragheto et al , 2007 ; Kim et al , 2007 ; Cho et al , 2008 ; Kang et al , 2009 ; Sheng et al , 2009 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhou et al , 2011 ; Kelekci et al , 2012 ; Ekin et al , 2013 ; Liu et al , 2014 ; Zhang et al , 2014 ; Huang et al , 2015 ; Lee et al , 2015 , 2019 ; Long et al , 2015 ; Chong et al , 2016 ; Liu et al , 2016 ; Park et al , 2016 ; Hai et al , 2017 ; Huang et al , 2017 ; Liu et al , 2017 ; Osuga et al , 2017 ; Yang et al , 2017 , 2019 ; Alizzi, 2018 ; Guo et al , 2018 ; Jun-Min et al , 2018 ; Li et al , 2018 , 2020 ; Huang et al , 2020 ; Lin et al , 2020 ; Sun et al , 2020 ; Kwack et al , 2021 ; Sun et al , 2021 ). There were six (16%) randomized controlled trials (RCTs) ( Hadisaputra and Anggraeni, 2006 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhang ...…”
Section: Resultsmentioning
confidence: 99%
“…There were six (16%) randomized controlled trials (RCTs) ( Hadisaputra and Anggraeni, 2006 ; Kang et al , 2010 ; Ozdegirmenci et al , 2011 ; Zhang et al , 2014 ; Osuga et al , 2017 ; Lin et al , 2020 ); 13 studies (34%) were prospective, non-randomized trials, of which nine had cohorts with a single arm ( Fedele et al , 1997 ; Bragheto et al , 2007 ; Kim et al , 2007 ; Cho et al , 2008 ; Sheng et al , 2009 ; Zhou et al , 2011 ; Ekin et al , 2013 ; Alizzi, 2018 ; Yang et al , 2019 ) and four studies had two or more arms ( Kelekci et al , 2012 ; Huang et al , 2015 ; Yang et al , 2017 ; Li et al , 2018 ). There were 17 (45%) retrospective cohort studies, 12 with a single arm ( Kang et al , 2009 ; Liu et al , 2014 , 2016 ; Lee et al , 2015 , 2019 ; Long et al , 2015 ; Chong et al , 2016 ; Park et al , 2016 ; Hai et al , 2017 ; Huang et al , 2017 ; Jun-Min et al , 2018 ; Kwack et al , 2021 ) and five with two or more arms ( Maia et al , 2003 ; Liu et al , 2017 ; Guo et al , 2018 ; Huang et al , 2020 ; Li et al , 2020 ). Two studies with a single cohort did not specify if the cohort was retrospective or prospective ( Sun et al , 2020 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…8,10,12,13 A 2-year follow-up study of 198 patients found similar improvement in pain scores and abnormal bleeding. 15…”
Section: Quality Of Lifementioning
confidence: 99%
“…13 These findings have been supported in other studies. 8,15,16 In a study of 224 patients undergoing abdominal and laparoscopic adenomyomectomy, there were no significant differences in dysmenorrhea rates at 7-month follow-up, though both treatment modalities appeared to be effective in treating dysmenorrhea when compared with baseline. 8…”
Section: Pelvic Painmentioning
confidence: 99%